Fabrication of Fluorine-Doped Tin Oxide (FTO): From experiment to its application in physics learning - Saehana, Sahrul; Izzah, Aqidatul; Palamba, Agnes Joisâ€™; Darsikin, Darsikin; Rahman, Nor Farahwahidah Abdul (Universitas PGRI Kanjuruhan Malang, 2023)
The paper reports the experiment in the laboratory in making FTO by employing spray pyrolysis methods, its application in DSSC, and its implementation in physics learning. The methodology in this research was mixed methods (experiment and qualitative methods). The experimental section was conducted by dissolving SnCl2.2H2O and NH4F in 96% alcohol and then depositioned on a glass substrate on a hotplate with a temperature of 450â—¦C using an Omron NE-C28 nebulizer. Spraying was carried out for 20 minutes then characterized morphology (SEM), content (EDS), crystal structure (XRD), transmittance (UV-VIS), and voltage-current (IV). Based on investigations using Scanning Electron Microscopy and Electron Dispersive Spectroscopy, it is known that transparent conductive SnO2:F particles have been formed. By using XRD, Nanometer-sized crystalline particles have also been identified. Furthermore, the FTO electrode is utilized as an electrode on DSSC and its performance is measured. In the qualitative section, students and researchers were interviewed about the physical aspect of the FTO fabrication process. Then, interview results were used to design laboratory physics learning.Â